Digital governance and its benchmarking college talent training under the rural revitalization in China—A case study of Yixian County (China) - Xing, Qinfeng; Yao, Wanyan (Frontiers in Public Health, 2022)
Rural digital governance has been the favorite subject of social governance with the aim of sustainable development of rural revitalization. Therefore, an indicator system is constructed to evaluate its satisfaction in Yixian County (China) based on principal component analysis, multiple regression analysis, and SEM structural equation analysis. The study finds that (1) the four dominant observation indicators, namely, “satisfaction of participation,” “satisfaction of diversification,” “satisfaction of legal norms,” and “satisfaction of technical support,” have a significant impact on the satisfaction of rural digital governance, and there is a linkage effect among the four observation indicators; (2) in terms of the four potential variables, “value guidance satisfaction” (0.772), “regulatory constraint satisfaction” (0.756), “satisfaction of support guarantee,” (0.699) and “multiple collaboration satisfaction” (0.676) have a decreasing influence on the overall satisfaction of rural digital governance, and there is much room for improvement. This study deepens the understanding of digital governance, and the following countermeasures are formed: strengthening the leading role of value concept; perfecting the constraint efficiency of “four governance” rule system; creating a new pattern of social “intelligent governance”; promoting the enabling effect of digital governance technology.